Translating the Qur'an in Palembang Vernacular: An Aesthetic Reception Theory Perspective on Surat An-Naziat - Agus Effendi; Syamsun Ni'am; Ngainun Naim; Ahmad Tholut Al-Faruq (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This article presents an analysis of the translation of the Qur'an into Palembang Language, with a focus on Surat An-Naziat. This research uses the perspective of Aesthetic Reception Theory to understand how Palembang language readers translate and receive this sacred text aesthetically. Through a qualitative approach, the author explores readers' aesthetic responses to this translation, covering elements such as the beauty of the language, appropriateness of the cultural context, and compatibility of the meaning with the original. The results of this analysis reveal how the Palembang language translation of Surat An-Naziat created a unique aesthetic experience for its readers, combining the richness of Palembang's language and local wisdom with the religious message of the Qur'an. This research makes an important contribution to understanding the process of translating the Qur'Än into local languages and explores the aesthetic aspects that play a role in fostering a deeper understanding of sacred texts in Palembang society.